Teachers’ Management in Implementation of CHED Memorandum Order (CMO) 39, Series of 2021 towards the Achievement of Students’ Learning Outcomes in Physical Education - John Michael Aquino (Physical Education and Sports: Studies and Research, 2023)
Background: The Commission on Higher Education (CHED) has issued Memorandum Order (CMO) No. 39, Series of 2021 that strengthens the management of physical education teachers and promotes the achievement of students’ learning outcomes. Higher education institutions will guarantee that they are adhering to the requirements of the CMO to ensure the quality of instruction in physical education and the improvement of the students’ learning outcomes. Objectives: This research aims to investigate the process of implementation of the CMO 39, Series of 2021 and its contribution to the improvement of student learning outcomes in Physical Education (PE). Methods: Through a qualitative research design based on a phenomenological approach, the researchers employed a purposive sampling method to select 9 male and 3 female PE teachers from Higher Learning Institution in the Philippines. A non-test instrument consisting of an interview guide was used to collect data from the study participants. The data was then analyzed to identify themes and patterns that emerged from the responses. Results: The study revealed the effectiveness of physical education in terms of student motivation, class orientation, students’ participation, and the application of the Physical Activity Towards Health and Fitness (PATHFIT) program. The findings show that physical education is an important part of the educational process and has a direct influence on the students' learning outcomes. Furthermore, the study also highlights the importance of providing students with the necessary knowledge and skills to succeed, and of assessing the students' abilities from their performance to achieve course objective with good behavior and attitude. Conclusion: It showed potential areas of improvement in the implementation process to ensure that the objectives of the memorandum are achieved, which is necessary for teachers to be aware of the competencies that need to be developed for students. This research will contribute to the existing literature on the importance of quality assurance programs, particularly in the area of physical education.